2022
DOI: 10.1111/hex.13568
|View full text |Cite
|
Sign up to set email alerts
|

Patient perspectives on primary care for multimorbidity: An integrative review

Abstract: Introduction Improving healthcare for people with multiple chronic or ongoing conditions is receiving increased attention, particularly due to the growing number of people experiencing multimorbidity (MM) and concerns about the sustainability of the healthcare system. Primary care has been promoted as an important resource for supporting people with MM to live well with their conditions and to prevent unnecessary use of health care services. However, traditional primary care has been criticized for not centrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 56 publications
(330 reference statements)
2
8
0
2
Order By: Relevance
“…Nepaisant to, poliligotumas lemia iššūkius, susijusius su kasdiene žmogaus veikla, pavyzdžiui, judėjimu, savipriežiūra, namų ruoša, darbu. Tai, kaip konkrečiam pacientui pavyksta susitvarkyti su gyvenimo pokyčiais susirgus, lemia, kaip jis vertins savo sveikatos būklę [8].…”
Section: įVadasunclassified
See 1 more Smart Citation
“…Nepaisant to, poliligotumas lemia iššūkius, susijusius su kasdiene žmogaus veikla, pavyzdžiui, judėjimu, savipriežiūra, namų ruoša, darbu. Tai, kaip konkrečiam pacientui pavyksta susitvarkyti su gyvenimo pokyčiais susirgus, lemia, kaip jis vertins savo sveikatos būklę [8].…”
Section: įVadasunclassified
“…Tačiau kiti tyrėjai pastebi, kad keletu lėtinių ligų sergantys vyrai, lyginant su moterimis, dažniau patiria problemų, susijusių su mobilumu, įprasta veikla, taip pat jie dažniau jaučia stipresnį skausmą [11]. Pažymima, kad blogesnis sveikatos būklės vertinimas priklauso ir nuo poliligotų pacientų žemesnio išsilavinimo, vyresnio amžiaus, vienišumo, pakitusios emocinės būsenos [8].…”
Section: įVadasunclassified
“…A systematic review and qualitative meta-synthesis of the lived experience of mental and physical multimorbidity identified only 19 published studies on this topic, all of which were from high-income countries 21. Another review on a similar topic identified 28 studies, none of which were from LMICs 22. A quick online search yielded one study exploring the lived experience of PLWMM in a LMIC, specifically Malawi 23.…”
Section: Introductionmentioning
confidence: 99%
“…Actively making complex care decisions and taking part in work, family and social life simultaneously can be overwhelming for chronically ill patients and their families. Such efforts are associated with high levels of psychosocial stress 1–3 . To maintain their participation in health care and social life, affected persons need support from health professionals 4–6 .…”
Section: Introductionmentioning
confidence: 99%
“…Such efforts are associated with high levels of psychosocial stress. [1][2][3] To maintain their participation in health care and social life, affected persons need support from health professionals. [4][5][6] Successful patient participation in health care is achieved when patients and health professionals cooperate in care as coproducers.…”
Section: Introductionmentioning
confidence: 99%